Topological Alterations of the Brain Functional Network in Type 2 Diabetes Mellitus Patients With and Without Mild Cognitive Impairment - Zhou, Baiwan; Wang, Xia; Yang, Qifang; Wu, Faqi; Tang, Lin; Wang, Jian; Li, Chuanming (Frontiers in Aging Neuroscience, 2022)
The aim of this study is to explore the topological alterations of brain functional network in type 2 diabetes mellitus (T2DM) with and without mild cognitive impairment (MCI) using resting-state functional magnetic resonance imaging (rs-MRI) and graph theory approaches. In total, 27 T2DM with MCI patients, 27 T2DM without MCI patients and 27 healthy controls (HCs) underwent a rs-fMRI scanning. The whole-brain functional network was constructed by thresholding the Pearson’s correlation matrices of 90 brain regions. The topological organization of the constructed networks was analyzed by using graph theory approaches. The global and nodal properties of the three groups were compared by using One-way ANOVA analysis as well as post hoc Tukey t-tests. The relationships between the altered topological properties and clinical features or scores of neuropsychological tests were analyzed in the T2DM with MCI patients. When compared with T2DM without MCI, the T2DM with MCI patients showed significant increased nodal properties in five brain regions, which mainly located in the orbitofrontal lobe and anterior cingulate gyrus (ACG) (P<0.05). No significant difference was found between the T2DM without MCI and HC subjects. Moreover, nodal degree (r = -0381, P = 0.050) and nodal efficiency (r = -0.405, P = 0.036) of the ACG showed significant closed correlation with the scores of Digit Span Backwards Test in the T2DM with MCI patients. In global level, the global and local efficiency of T2DM with MCI group was significantly higher than that of the HC group, and the length of characteristic path was significantly lower than that of the HC group (P < 0.05). No significant difference was found between the other groups. Our results suggested that the increased nodal properties in brain regions of orbitofrontal lobe and ACG were biomarkers of cognitive impairment in T2DM and could be used for its early diagnosis. The global topological alterations may be related with the combination of MCI and T2DM, rather than any of them.